Marble Beyond the Vein. For an Alternative Semiotics of Materials - Festi, Giacomo (E|C, 2023)
The research presented here starts from an experience of collaboration with the company of Lasa Marmo in Val Venosta, within the framework of a didactic/experimental project of the University of Bolzano, in the design area. Lasa Marmo covers the entire production chain of marble, from quarrying, to processing, to the production of slabs to be placed on the market, mainly addressed to the world of architects, i.e. a further trajectory of processing aimed at site-specific installations. Against this design background, the research grafts a reconsideration of the status of the semiotics of materials. Semiotics has looked at them through the main filter of aesthetics, without forgetting metaphorical convocations, in a more epistemological key. Marble is a striking example of this, starting with its veins, conceived as lines of resistance of the being to be grasped (negatively) from an operability of the materials themselves (the cut). The contribution relocates the semiotics of materials within the framework of a dialogue with design practices on the one hand (Material Driven Design in particular) and with material historians on the other (Bensaude-Vincent), in order to renew the semiotic scientific project. Characterising marble then means not only showing its possible plastic qualities, but also highlighting its paradoxes on an ecosystemic level, between perenniality and instability, sustainability and extraction, iconodulia and iconoclasm. Sustainability, in particular, will become the thematic pivot of a targeted study, linked to the projects of some students throughout the semester. The marble is going to reveal itself as the quintessential material for semioticians, given its unpredictable richness of semiotic possibilities.